NOCTUA suite of simulations: the difficulty of growing massive black holes in low-mass dwarf galaxies - Petersson, Jonathan; Hirschmann, Michaela; Tress, Robin G.; Farcy, Marion; Glover, Simon; Klessen, Ralf S.; Naab, Thorsten; Partmann, Christian; Whitworth, David J. (Astronomy and astrophysics, 2025)
Aims. We study the individual and cumulative impact of stellar feedback on massive black hole (MBH) growth in a simulated low-mass dwarf galaxy. Furthermore, we explore the influence of the MBH’s initial mass (103−6 M⊙) on the gas accretion, and whether or not artificially induced gas inflows can ‘boost’ further gas accretion onto the MBH. Methods. A suite of high-resolution radiation-hydrodynamic simulations called NOCTUA were performed, using the AREPONOCTUA numerical framework. The chemical evolution of the interstellar medium (ISM) was modelled in a time-dependent non-equilibrium way. Two types of stellar feedback were considered: individually traced type II supernova (SNII) explosions, and radiatively transferred (on-the-fly) ionising stellar radiation (ISR) from OB stars. As part of AREPONOCTUA, we develop and apply a novel physically motivated model for MBH gas accretion, taking into account the angular momentum of the gas in the radiatively efficient regime, to estimate the gas accretion rate onto the MBH from its sub-grid accretion disc. Results. Without any stellar feedback, an initial 104 M⊙ MBH is able to steadily grow over time, roughly doubling its mass after 800 Myr. Surprisingly, the growth of the MBH more than doubles when only ISR feedback is considered, compared to the no stellar feedback run. This is due to the star formation rate (SFR) being highly suppressed (to a similar level or slightly above that when SNII feedback is considered), enabling a higher cumulative net gas inflow onto the MBH from not only the cold neutral and molecular medium phases, but also the unstable and warm neutral medium phases of the ISM. With SNII feedback included, the gas accretion onto the MBH is episodic over time, and is already suppressed by more than an order of magnitude during the first 150 Myr. When combining SNII with ISR feedback, the growth of the MBH remains suppressed due to SNII explosions, but to a lesser extent compared to the SNII-only feedback run, due to a slightly lower SFR, and thus a reduced number of SNII events. Conclusions. We conclude that SNII feedback is a strong regulator and suppressor of MBH growth, and that only an initial 105 M⊙ MBH is able to consistently accrete gas in the radiatively efficient regime (in the presence of SNII feedback). Combined with the fact that artificially induced gas inflows are unable to boost further gas accretion onto the MBH (even for an initial 106 M⊙ MBH), this suggests that it is primarily the nearby gravitational potential around the MBH that determines how much the MBH can grow via gas accretion over time (at least in an isolated non-cosmological environment).
Online veröffentlicht: 09. Dezember 2025
Gesehen am 18.02.2026